1985
DOI: 10.1159/000194746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Hemoglobin Levels on the Diffusing Capacity of the Lungs for CO

Abstract: The influence of the hemoglobin concentration in the peripheral venous blood on the diffusing capacity of the lungs for CO (DLCO) was tested with the single-breath method. 9 patients with histologically verified interstitial pulmonary fibrosis of varying etiology and 26 persons with healthy lungs with anemia requiring transfusions were investigated before and after compensation of the anemia. It was found that the true maximum diffusing capacity of the lungs measured in anemia patients was too low. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Heard [23] and Perry et al [24] have described parenchymal fibrosis and fibrin masses in the air spaces of chronic uremic patients which could lead to alveolar-capillary block and the DLCO reduction. Since our results are in agreement with Peterman's data [7], it is possible that in uremic patients on chronic HD with 'healthy lungs' (diagnosed radiologically and spirometrically) the DLCO reduction is a function of coexisting ane mia and low Hb levels. A possible explanation for HD-induced DLCO reduction may be HD-induced decreased pulmonary perfusion, as evidenced by de creased Vc.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Heard [23] and Perry et al [24] have described parenchymal fibrosis and fibrin masses in the air spaces of chronic uremic patients which could lead to alveolar-capillary block and the DLCO reduction. Since our results are in agreement with Peterman's data [7], it is possible that in uremic patients on chronic HD with 'healthy lungs' (diagnosed radiologically and spirometrically) the DLCO reduction is a function of coexisting ane mia and low Hb levels. A possible explanation for HD-induced DLCO reduction may be HD-induced decreased pulmonary perfusion, as evidenced by de creased Vc.…”
Section: Discussionsupporting
confidence: 92%
“…Dinkara et al [6] reported that a reduction of Hb lev el by 10 g/1 resulted in a decrease of the DLCO by 7%. Investigating the influence of Hb concentration on DLCO and the effect of BT in patients with anemias of various etiologies, Peterman [7] reported similar findings. Based on the mean value of Hb of 145 g/1 for men and women, the present study showed that a 10-g/1 change in Hb concentration caused by transfusion corresponded to a 7.2% change in the DLCO.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies examining the effect of just anaemia or anaemia combined with disorder of the alveolocapillary membrane consistently mention that anaemia does affect the diffusion capacity, but the defect of the respiratory membrane on diffusing capacity is greater. 22 23 In this study, we have patients with COPD and anaemia who commonly also have defect with the respiratory membrane, both contributing to the reduced DLco as noted. We think that the initial poor correlation with blood gases in this study is because the compensatory mechanisms are not yet fully dysfunctional and the anaemia not severe.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that Hb can affect the oxygen carrying capacity of blood in circulation. 20 In the case of anemia, the oxygen carrying capacity decreases and the respiratory function changes accordingly. This helps explain our finding of higher respiratory rate in patients with anemia.…”
Section: Discussionmentioning
confidence: 99%